Analisis Yuridis Wanprestasi Pembayaran Iuran Jaminan Kesehatan Nasional oleh Badan Usaha: Studi Kasus Kantor BPJS Kesehatan Cabang Singaraja - Andres Avelino Johan Simatupang (Lembaga Pengembangan Kinerja Dosen, 2026)
The participation of business entities in the National Health Insurance (JKN) program is a constitutional obligation that is explicitly regulated in Indonesia's social security system regulations. However, in its implementation, the phenomenon of default in the form of non-compliance with premium payments by business entities remains a significant obstacle that hinders the optimization of health services. This study aims to analyze the factors causing default on BPJS Kesehatan premium payments by business entities in the Singaraja Branch Office's working area and to examine the legal remedies pursued from a business law perspective. The research method used is empirical legal research with a sociological juridical approach. The results of the study show that corporate economic factors, low legal awareness among employers, and internal administrative constraints are the main triggers of default. Resolution efforts are carried out through administrative approaches, persuasive mediation through the REHAB Program, and legal enforcement through litigation and non-litigation involving State Attorneys from the Buleleng District Attorney's Office. This collaborative step is essential to ensure that workers' constitutional rights to health insurance are fulfilled amid the challenges of local business dynamics.